Effect of socioeconomic status on objectively measured physical activity. Issue 1 (20th October 2005) - Kelly, L A; Reilly, J J; Fisher, A; Montgomery, C; Williamson, A; McColl, J H; Paton, J Y; Grant, S
Abstract : Background: A socioeconomic gradient in childhood obesity is known to be present by the age of school entry in the UK. The origin of this gradient is unclear at present, but must lie in socioeconomic differences in habitual physical activity, sedentary behaviour, or dietary intake. Aims: To test the hypothesis that habitual physical activity and/or sedentary behaviour are associated with socioeconomic status (SES) in young Scottish children. Methods: Observational study of 339 children (mean age 4.2 years, SD 0.3) in which habitual physical activity and sedentary behaviour were measured by accelerometry over six days (study 1). In a second study, 39 pairs of children of distinctly different SES (mean age 5.6 years, SD 0.3) were tested for differences in habitual physical activity and sedentary behaviour by accelerometry over seven days. Results: In study 1, SES was not a significant factor in explaining the amount of time spent in physical activity or sedentary behaviour once gender and month of measurement were taken into account. In study 2, there were no significant differences in time spent in physical activity or sedentary behaviour between affluent and deprived groups. Conclusion: Results do not support the hypothesis that low SES in young Scottish children is associated with lower habitual physical activity or higher engagement in sedentary behaviour.